Формування і розвиток професійних компетенцій майбутніх економістів при вивченні дисциплін комп’ютерного циклу - Болюбаш, Н. М. (НТУ "ХПІ", 2010)
В статье в рамках компетентностного подхода осуществлено выделение наиболее значимых для профессионального становления будущих экономистов ключевых компетенций и установлен перечень информационных компетенций, которые формируются в процессе изучения дисциплин компьютерного цикла. Ключевые слова: профессиональная компетентность, компетенция, ключевые компетенции, базовые компетенции, информационные компетенции.

The article is based on competence approach to vocational training the future economists. In article is allocated key competences and is established the list of information competences that are formed at studying of disciplines of the computer cycle. Keywords: professional competence, competence, key competences, base competences, information competences.
Formation and development of professional competences of the future economists at studying of disciplines of the computer cycle
Keywords: професійна підготовка; компетентнісний підхід; ціннісні орієнтації; науковці; освітні стандарти; ключові компетенції